Exploring Restrictions to use of community greenways for physical activity through structural equation modeling - Erkang Fu; Xiaoyu Deng; Yuanhao Wu; Lin Li; Yilin Xiong; Mengzhou Li; Zihan Zhang; Juan Du; Xinyun Li; Xi Li (Frontiers Media S.A., 2023)
Public health problems caused by rapid urbanization have attracted increasing amounts of attention. Existing studies show that improving the frequency and duration of physical activity among urban residents can effectively reduce their disease risk. A community greenway, as a green space for public activity directly serving community residents, is one of the best spatial place for bringing health benefits to people. Although the scale and scope of greenway construction have been increasing in recent years, the utilization rate of some greenways is not high for various reasons, restricting the extent to which people engage in healthy physical activities in greenway spaces. In this study, the greenway of Nancheng Community in Wenjiang District, Chengdu city, China was selected as the object of study, and structural equation modeling was conducted to explore the objective environmental factors and individual characteristics acting as barriers to use of the community greenway by the population for physical activity. The results show that user experience, the greenway landscape, and safety and accessibility are important factors that restrict people's willingness engage in physical activity in the community greenway environment. The results of this study provide a direction for further consideration of ways to enhance people's willingness to make use of greenways for physical activity, and further provide a theoretical basis for the healthy design and transformation of community greenway spaces.